2009
DOI: 10.2134/agronj2007.0031
|View full text |Cite
|
Sign up to set email alerts
|

Potato Yield and Quality Response to Subsoil Tillage and Compaction

Abstract: Compacted soils have been found in intensively cultivated vegetable crop regions of Central Wisconsin, resulting in the wide scale use of subsoil tillage by growers. Th e goal of this project was to assess potato (Solanum tuberosum L.) yield and quality response to soil compaction and subsoil tillage. Potato quality factors evaluated were marketable yield, tuber size distribution, internal quality, and sugar concentration. A controlled small plot experiment and several fi eld scale experiments located in colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…It should be noted that subsoiling is only relevant when it breaks a compacted soil layer, and in many of these experiments the level of compaction prior to cultivation was not described. In a more recent study by Copas et al (2009), under controlled compaction levels, no consistent effects of subsoil tillage was reported and support the conclusions by Stalham et al (2005). There are, however, also reports of significant yield increases following subsoiling.…”
Section: Soil Compaction Effects In Potatoessupporting
confidence: 74%
“…It should be noted that subsoiling is only relevant when it breaks a compacted soil layer, and in many of these experiments the level of compaction prior to cultivation was not described. In a more recent study by Copas et al (2009), under controlled compaction levels, no consistent effects of subsoil tillage was reported and support the conclusions by Stalham et al (2005). There are, however, also reports of significant yield increases following subsoiling.…”
Section: Soil Compaction Effects In Potatoessupporting
confidence: 74%
“…Compacted soils reduced the plant height of field corn, and decreased the aboveground biomass in potato, snap bean, cucumber, and cabbage [45]. Subsoil tillage has been recommended to use across the United States to alleviate the negative effect of a compacted layer on potato (Solanum tuberosum L.) productivity [46]. Compared with no-till plots, subsoil tillage dramatically decreased foliar symptoms of sudden death syndrome for soybeans [47].…”
Section: The Effect Of Subsoil Tillage On Economic Efficiencymentioning
confidence: 99%
“…Copas, Bussan, Drilias, and Wolkowski (2009) conducted a controlled small‐plot experiment and field‐scale experiments in loamy sand soils to assess the responses of potato yield and quality and soil physical properties to subsoil tillage for 3 consecutive yr. In the small‐plot experiment, soil strength as measured by penetration resistance of a compacted soil treatment (achieved by repeatedly driving a heavily loaded truck and attaining a penetration resistance of ≥435 psi) was significantly higher than non‐compacted treatments throughout the soil profile.…”
Section: Subsoiling As a Remedial Measure For Compaction In Potato Prmentioning
confidence: 99%
“…However, just as many studies have shown that both tuber yield and quality were either unaffected or slightly reduced by subsoiling, even in severely compacted soils (Buxton & Zalewski, 1983; Copas et al., 2009; Henriksen, Mølgaard, & Rasmussen, 2007; Holmstrom & Carter, 2000). Such results are often attributed to clod formation, reconsolidation, high moisture content during bedding, topographic variations, and compaction variation among wheel‐trafficked and non‐trafficked furrows.…”
Section: Subsoiling As a Remedial Measure For Compaction In Potato Prmentioning
confidence: 99%